IMPLEMENTASI KEBIJAKAN SMART CITY: PERAN DINAS KOMUNIKASI DAN INFORMATIKA KABUPATEN KUTAI KARTANEGARA - Adi Sucipto (Jurnal Administrative Reform, 2022)
Implementation of the Smart City in Kutai Kartanegara is not easy. This is due to the vast geographical conditions with minimal access to transportation and there are still isolated areas. Until 2021, there are still 13 village blank spots. From the institutional view, the biggest challenge arises from the low understanding and ability of the State Apparatus in utilizing the digitization of information technology-based services. Based on the above conditions, this study aims to examine more deeply the role of the Dinas Komunikasi dan Informatika in Kutai Kartanegara Regency in supporting the implementation of Smart City policies. The method used in this research is descriptive qualitative with an analytical framework based on Edward III's theory which consists of aspects of communication, resources, disposition, and organizational structure. The results of this study indicate that as a supporting Regional Apparatus Organization, the role of Diskominfo Kutai Kartanegara in the implementation and socialization of Smart City has not been optimal. This can be seen from the aspect of resources, it was found that most of the Civil Apparatus at Diskominfo do not have knowledge in the field of information technology. Meanwhile, from the aspect of disposition, policy makers have formed a Regent Regulation as the institutes for Smart City. In the aspect of bureaucratic structure, the role of the supervisory and control function of Diskominfo in each field is still not running. Strategic steps are needed so that the Smart City policy is included in the Diskominfo budget planning document.